"A world crazier than us": Vanishing social contexts and the consequences for psychiatric practice in contemporary Romania. (April 2016) - Friedman, Jack R.
Since the end of Communism, mental health care in Romania has increasingly sought to align its practices with idealized models of Western psychiatric practice. Much of this realignment has been made possible by accessing and integrating new pharmaceuticals into psychiatric hospital settings. Less straightforward have been the painful attempts to create a system modeled on international standards for training and certifying psychotherapists. Unfortunately, the political, economic, infrastructural, and epistemological environment of the Romanian mental health care system has prevented many other reforms. This paper examines the ironic trajectory that Romanian psychiatry has taken since the end of state socialism. Specifically, this paper shows how psychiatric practice in most places (outside of university-training hospitals) is increasingly disconnected from a concern with the social conditions that surround mental illness during a period when social upheaval is profoundly impacting the lives of many people who receive mental health care. Thus, as the contribution of social problems to the suffering of those with mental illnesses has increased, some Romanian mental health practitioners have moved away from a concern with these social problems under the guise of aligning their psychiatric practices with (imagined) Western standards of biomedical care. The paper provides a brief history of Romanian psychiatry and explores contemporary challenges and contradictions in many Romanian psychiatric treatment settings through the case study of a 31-year-old Romanian female diagnosed with paranoid schizophrenia.